ANALISIS KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DALAM MENYELESAIKAN SOAL ETNOMATEMATIKA DI MIM GIRIMARGO SRAGEN - Aprilia Kusuma Pertiwi; Ema Butsi Prihastari; Sugiaryo Sugiaryo (FKIP, PGSD, Universitas Slamet Riyadi, 2021)
The focus of this research is to 1) analyze learners' creative thinking skills and 2) identify the variables that restrict learners' capacity to think creatively in addressing ethnomathematics issues at MIM. Sragen, Girimargo The research method employed is qualitative research with analytical study methodologies. This study's participants were class V students, instructors, and parents. Interviews, observations, and documentation were utilized to collect data. A qualitative descriptive interaction model is used in this study's data analysis approach. The findings of this study are as follows: (1) learners with good mathematical skills and the capacity to think creatively at level 3 are creative, whereas learners with low mathematical skills and the ability to think creatively at level 1 are less creative. (2) Communication, laziness, and a lack of desire are variables that impede learners' capacity to think creatively while addressing ethnomathematics issues. Lack of mental freedom, as well as a lack of material resources.